PENANGKAPAN IKAN DENGAN BOM DI DAERAH TERUMBU KARANG DESA ARAKAN DAN WAWONTULAP - Pontoh, Otniel (Sam Ratulangi University, 2011)
This study was aimed to see the behavior of fishermen who catch fish using explosives in coral zone. This research was carried out in Arakan and Wawontulap villages, South Minahasa.Â The results showed that almost 60 percent of coral reef areas were destroyed by fish bombing.